Live genome imaging by CRISPR engineering: progress and problems - Eui-Jin Park; Hajin Kim (Experimental and Molecular Medicine)
Abstract CRISPR–Cas-based genome imaging opened a new era of genome visualization in living cells. While genomic loci with repetitive sequences, such as centromeres and telomeres, can be reliably imaged, applying the technique to nonrepetitive genomic loci has remained challenging. Recent advancements in the design of CRISPR RNAs and Cas proteins, the development of novel fluorophores and the combination of CRISPR–Cas with other molecular machinery amplified target-specific signals and suppressed background signals, revolutionizing this unique genome imaging technique and enabling the tracking of genomic loci with a small number of CRISPR–Cas complexes, down to a single complex. Here we review the latest advancements in CRISPR–Cas-based genome imaging techniques and their application to imaging nonrepetitive genomic loci. The challenges that these techniques are currently facing are the cellular toxicity and genomic instability induced by the expression of CRISPR–Cas and its interference with DNA metabolism, which impacts DNA replication and genome maintenance. Recently reported adverse effects of CRISPR–Cas-based genome labeling are discussed here, along with perspectives on how to overcome the problem.